MIŁOSIERDZIE A MISTERIUM PASCHALNE W TEOLOGII JANA PAWŁA II RELACJA, SKUTEK, IMPLIKACJE - Dudek-Kowalska, Agnieszka (Studia Pastoralne, 2023)
As the purpose of the article unveiled above the author was going to show mysterium paschale interpreted by the Pope John Paul II through the prism of the theology of God’s mercy. The essential lecture of this subject can be found in the two first encyclicals of the Pope: Dives in misericordia and Redemptor hominis, however the problem was consequently present in the teaching of the Pope during his whole pontificate. In the presented article the author tries to unveil the perspective of God’s mercy in the mystery of the cross and Christ’s resurrection. Within each of these issues the author unveiled the problems that were special and complete expression of the merciful love of God. Within the question of the relation between the mystery of the cross and the mystery of God’s mercy the following problems were touched: acceptance of the suffering of Christ as an expression of solidarity with the creature, discovery of God who deserves mercy, the kenosis of the Son as the revelation of God’s mercy, the fidelity of God to the creature. In the elaboration of the problem of God’s mercy in the resurrection of Christ the following issues were touched: the Father’s mercy toward the Son, the God’s mercy towards the creature, the sign and the beginning of the eschatological mercy.